Proteome profiling of the compatible interaction between wheat and stripe rust - Demirci, Yahya Emin; Inan, Cihan; Gunel, Aslihan; Maytalman, Dilara; Mert, Zafer; Baykal, A. Tarik; Korkut, Senay Vural; Arda, Nazli; Hasancebi, Semra (SPRINGER, 2016)
Over the last decade, comparative molecular profiling studies between compatible and incompatible plant-pathogen interactions have shown that susceptible response of the host to a pathogen requires factors that promote disease development. In this study, we examined proteome profiles during a compatible interaction between wheat and stripe rust. A 2D-LC system (ProteomeLab PF2D) was used for protein separation and to compare the proteome from infected and control samples. More than 700 protein peaks at each time point were compared between pathogen- and mock-inoculated samples. Selected proteins, with significant differences in abundance were identified by nanoLC-ESI- MS/MS and generated spectra were searched against the wheat protein databases from UniProt, and NCBI and the Puccinia database from The Broad Institute. In total, the identified proteins comprised of 62 % wheat and 38 % Pst proteins. All identified proteins were searched by bioinformatics-based algorithms to detect their subcellular localization and signal peptide motifs which have the potential to catch the candidate effector proteins. The wheat proteins were classified based on their function. Although a compatible interaction, many wheat proteins, such as antioxidants, PRs and cold-responsive proteins, are implicated in defense and stress tolerance. On the pathogen side, 64 proteins were identified, and included some important pathogenicity proteins that can play role in pathogen virulence and suppress the host defense. In addition, we discovered that nine proteins have a signal sequence and three of the hypothetical fungal proteins, PGTG_11681T0, PGTG_07231T0 and CBH50687.1, have been tentatively identified as candidate effectors.
Keywords: Disease; Effector; Fungal proteins; Wheat; Plant-pathogen interaction; Puccinia striiformis; PATHOGENESIS-RELATED PROTEINS; LIPID TRANSFER PROTEIN; GENE-EXPRESSION; INCOMPATIBLE INTERACTIONS; ANTIFUNGAL ACTIVITY; DISEASE RESISTANCE; TRITICUM-AESTIVUM; OXIDATIVE STRESS; HEXAPLOID WHEAT; DEFENSE; Agriculture; Plant Sciences